Lessons learned from microsatellite development for nonmodel organisms using 454 pyrosequencing. (17th January 2013) - Schoebel, C. N.; Brodbeck, S.; Buehler, D.; Cornejo, C.; Gajurel, J.; Hartikainen, H.; Keller, D.; Leys, M.; Říčanová, Š.; Segelbacher, G.; Werth, S.; Csencsics, D.
Abstract: Microsatellites, also known as simple sequence repeats (SSRs), are among the most commonly used marker types in evolutionary and ecological studies. Next Generation Sequencing techniques such as 454 pyrosequencing allow the rapid development of microsatellite markers in nonmodel organisms. 454 pyrosequencing is a straightforward approach to develop a high number of microsatellite markers. Therefore, developing microsatellites using 454 pyrosequencing has become the method of choice for marker development. Here, we describe a user friendly way of microsatellite development from 454 pyrosequencing data and analyse data sets of 17 nonmodel species (plants, fungi, invertebrates, birds and a mammal) for microsatellite repeats and flanking regions suitable for primer development. We then compare the numbers of successfully lab‐tested microsatellite markers for the various species and furthermore describe diverse challenges that might arise in different study species, for example, large genome size or nonpure extraction of genomic DNA. Successful primer identification was feasible for all species. We found that in species for which large repeat numbers are uncommon, such as fungi, polymorphic markers can nevertheless be developed from 454 pyrosequencing reads containing small repeat numbers (five to six repeats). Furthermore, the development of microsatellite markers for species with large genomes was also with Next Generation Sequencing techniques more cost and time‐consuming than for species with smaller genomes. In this study, we showed that depending on the species, a different amount of 454 pyrosequencing data might be required for successful identification of a sufficient number of microsatellite markers for ecological genetic studies.